قاعدة لا ضرر ولا ض ا رر وأثرها في فقه الأسرة "نماذج مختارة" - أوبیش, مسعودة (University of eloued جامعة الوادي, 2016)
هذا البحث بعنوان: قاعدة لا ضرر ولا ض ا رر وأثرها في فقه الأسرة"نماذج مختارة"، یبین مدى اعتبار العلماء لهذه القاعدة، وبیان أثرها في فقه الأسرة. احتوى هذا البحث على فصلین، عني الفصل الأول بالد ا رسة النظریة، وذلك ببیان مفهوم القاعدة الفقهیة، ثم التعریف بقاعدة لا ضرر ولا ض ا رر، وخَلصُ إلى أن هذه القاعدة من القواعد الأساسیة الكبرى، متفق علیها عند الفقهاء، وصالحة للاحتجاج بها؛ لأن أصلها حدیث نبوي شریف، أما الفصل الثاني فعني ببیان أثر قاعدة لا ضرر ولا ض ا رر في فقه الأسرة؛ لأنها نواة المجتمع الإسلامي،وذلك بذكر نماذج في فترة الخِطبة وأخرى في فترة الزواج، وبیان أثر هذه القاعدة فیها.وتوصل البحث في الأخیر إلى أن الضرر مدفوع في الشریعة الإسلامیة، سواء قبل أو بعد وقوعه، وتبین ذلك من خلال النماذج المختارة.This research titled: Base do no harm and its impact on the jurisprudence of the family "selected models", shows the extent to which the scientists to this rule, and the statement of its impact in the jurisprudence of the family. Contained this research on two chapters, Me first chapter theoretical study and that a statement on the concept of doctrinal base, then the definition of base do no harm, and resulted to be the rule of the major basic rules, agreed upon scholars, and are valid for a protest by; because the origin of modern NabaWi Sharif, the second chapter Fna statement on the impact of the base do no harm in the jurisprudence of the family; because it is the nucleus of the Muslim community, and by mentioning models in the period of the engagement and the other in the marriage, and the statement of the impact of this rule there. The research found that in the last damage paid in Islamic law, either before or after the fact, and show through selected models.
ماستر دعوة
Keywords: فقه الأسرة,قاعدة,ضرر,ضر ار; Family jurisprudence, rule, harm